Evaluation of the Implementation of the Tourism Village Program in Economic and Environmental Development (Study in Pasar Seluma Village, Seluma Regency, Bengkulu Province) - Nabila Nur Syafiah; Henny Aprianty; Hernowo Novy Yanto (Journal GoodWill, 2025)
This study aims to evaluate the implementation of the tourism village program in Pasar Seluma Village, Seluma Regency, Bengkulu Province, with a focus on its contribution to community economic development and environmental conservation. The tourism village program is expected to serve as a sustainable development strategy based on local potential. The research method employed is descriptive qualitative, with data collected through in-depth interviews, observation, and documentation. The research informants consist of 10 individuals, including the village head, village officials, tourism managers (Pokdarwis and BUMDes), MSME actors, community leaders, and local residents. Data analysis was carried out using the CIPP model (Context, Input, Process, Product) developed by Stufflebeam, and further analyzed with the interactive model of Miles, Huberman, and Saldana (data reduction, data display, and conclusion drawing). Data validity was tested through source and technique triangulation. The findings indicate that the tourism village program has had a positive impact in creating economic opportunities and increasing community income through small businesses and the promotion of local potential. However, the program’s implementation still faces challenges, including limited infrastructure, low community awareness of environmental conservation, and limited human resource capacity. In terms of the environment, greater community participation is needed to protect tourist areas, especially the beach, from ecological damage. Therefore, it is necessary to strengthen local institutions, enhance support from local government, and provide continuous training and socialization to realize a tourism village that is economically and environmentally sustainable.